2019
DOI: 10.1016/j.jpeds.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors in Offspring of Preeclamptic Pregnancies—Systematic Review and Meta-Analysis

Abstract: Study design PubMed, the Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, and EMBASE electronic databases were searched with an end of search date of June 4, 2018. Prospective and retrospective studies that compared CVD risk factors in those exposed to preeclampsia in utero with controls were eligible. Information was extracted on established CVD risk factors, including blood pressure, lipid profile, blood glucose, fasting insulin, body mass index, and endothelial/microvascular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 61 publications
4
62
0
Order By: Relevance
“…1 University of Helsinki, Finland; 2 National Institute for Health and Welfare, Helsinki, Finland; 3 University of Edinburgh, United Kingdom; 4 Erasmus Medical Center, Rotterdam, the Netherlands; 5 University of Turku, Finland; 6 University of Helsinki and Helsinki University Hospital, Finland; 7 Hyvinkää Hospital, Finland; 8 Oulu University Hospital and University of Oulu, Finland; 9 Norwegian University for Science and Technology, Trondheim, Norway; 10 University of Tampere, Finland.…”
Section: Data Supplement Maternal Hypertensive Pregnancy Disorders Anmentioning
confidence: 99%
See 1 more Smart Citation
“…1 University of Helsinki, Finland; 2 National Institute for Health and Welfare, Helsinki, Finland; 3 University of Edinburgh, United Kingdom; 4 Erasmus Medical Center, Rotterdam, the Netherlands; 5 University of Turku, Finland; 6 University of Helsinki and Helsinki University Hospital, Finland; 7 Hyvinkää Hospital, Finland; 8 Oulu University Hospital and University of Oulu, Finland; 9 Norwegian University for Science and Technology, Trondheim, Norway; 10 University of Tampere, Finland.…”
Section: Data Supplement Maternal Hypertensive Pregnancy Disorders Anmentioning
confidence: 99%
“…1-2 They are key risk factors for maternal mortality, 1-2 stillbirth, 1,3 preterm birth 1, 3 and intrauterine growth restriction (IUGR), 3 and predict cardiovascular morbidity in the mother and her offspring. [1][2][3][4] Increasing evidence suggests that the offspring risk is not confined to perinatal and cardiovascular health. Rather, maternal hypertensive pregnancy disorders also predict increased offspring risk of mental disorders, psychiatric symptoms and neurodevelopmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the risk of HDP is elevated following ART , Thomopoulos et al, 2013, Opdahl et al, 2015, Maheshwari et al, 2018, not least in frozen cycles, thus ART might also be a potential risk factor for the development of CVD in the offspring. A meta-analysis including 36 studies on 53,000 individuals showed that in utero exposure to preeclampsia was associated with a 5.17 mm Hg higher mean systolic and 4.06 mm Hg higher mean diastolic blood pressure as well as a slightly higher (0.36 kg/m 2 ) mean BMI in children and young adults (Andraweera and Lassi, 2019). Both elevated blood pressure and changes in body composition have been found after ART in a few studies (Ceelen et al, 2009, Scherrer et al, 2015, Meister et al, 2018 and summarized in systematic reviews and meta-analyses (Hart andNorman, 2013, Guo et al, 2017).…”
Section: Cardiovascular Risksmentioning
confidence: 99%
“…We recently conducted a systematic review and meta-analysis of prospective and retrospective studies that had compared CVD risk factors among those exposed to PE in utero compared to those not exposed to PE in utero. 9 This pooled evidence from 36 studies and over 53,000 participants found that systolic blood pressure, diastolic blood pressure and body mass index (BMI) were significantly higher among those exposed to PE in utero compared to those not exposed to PE in utero. 9 The link between maternal PE and offspring CVD is likely to be due to abnormalities in vascular function.…”
Section: Introductionmentioning
confidence: 99%
“…9 This pooled evidence from 36 studies and over 53,000 participants found that systolic blood pressure, diastolic blood pressure and body mass index (BMI) were significantly higher among those exposed to PE in utero compared to those not exposed to PE in utero. 9 The link between maternal PE and offspring CVD is likely to be due to abnormalities in vascular function. This is supported by the finding of impaired vascular responses in some offspring animal models that mimic PE 10 as well as the majority of human studies of those exposed to PE in utero.…”
Section: Introductionmentioning
confidence: 99%